2004
DOI: 10.1097/01.sap.0000128087.51384.f9
|View full text |Cite
|
Sign up to set email alerts
|

Silicone Breast Implants and Connective Tissue Disease

Abstract: Numerous meta-analyses, weight-of-the-evidence, and critical reviews have summarized data from case-control and cohort studies, published through 1999, which have been conducted to evaluate the potential association between cosmetic silicone breast implants and the occurrence of well-defined connective tissue diseases, as well as a hypothesized new atypical disease, which does not fulfill established diagnostic criteria for any known connective tissue disease. These reviews have unanimously concluded that ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(7 citation statements)
references
References 16 publications
1
4
0
2
Order By: Relevance
“…There are few reports suggesting that silica exposure can precede the onset of SS especially in certain chronically exposed professional groups, such as dental technicians [ 75 , 76 ] and coalminers [ 77 , 78 , 79 ]. The association between silicone breast implants and autoimmune diseases still remains inconclusive considering data from systematic reviews and meta-analyses [ 80 , 81 , 82 ]. A more recent post-approval long-term outcome study on an extremely large cohort suggests that there are higher rates of SS and other autoimmune disorders in patients undergoing silicone breast implants [ 83 ].…”
Section: Classical Examples Of the Asia Syndromementioning
confidence: 99%
“…There are few reports suggesting that silica exposure can precede the onset of SS especially in certain chronically exposed professional groups, such as dental technicians [ 75 , 76 ] and coalminers [ 77 , 78 , 79 ]. The association between silicone breast implants and autoimmune diseases still remains inconclusive considering data from systematic reviews and meta-analyses [ 80 , 81 , 82 ]. A more recent post-approval long-term outcome study on an extremely large cohort suggests that there are higher rates of SS and other autoimmune disorders in patients undergoing silicone breast implants [ 83 ].…”
Section: Classical Examples Of the Asia Syndromementioning
confidence: 99%
“…This has been the subject of some debate as many reports have found no increased risk, including a large case-control study on the risk of SLE with silicone implants [74]. A recent review of a number of case-control studies, cohort studies and critical reviews summarized that there is no connection between connective tissue diseases, including RA, SLE and Scl, and silicone implants [75]. Even if there was a risk for women who have implants, given the prevalence of autoimmune diseases and the proportion of women with implants, it is unlikely that this risk factor is substantial enough to make a difference to disease incidence.…”
Section: Environmental Differencesmentioning
confidence: 99%
“…They described fatigue, joint pain, and cognitive impairment as the most common symptoms [ 24 , 27 ]. A systematic review by Lipworth et al [ 9 ] reported similar findings.…”
Section: Discussionmentioning
confidence: 63%